2021
DOI: 10.3390/ijms222111471
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of the Zebrafish K+ Channel Hcn2b Exhibit Epileptic-like Behaviors

Abstract: Epilepsy is a chronic neurological disorder that affects 50 million people worldwide. The most common form of epilepsy is idiopathic, where most of the genetic defects of this type of epilepsy occur in ion channels. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are activated by membrane hyperpolarization, and are mainly expressed in the heart and central and peripheral nervous systems. In humans, four HCN genes have been described, and emergent clinical data shows that dysfunctional HCN ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The response of the larvae to dark–light–dark transitions was evaluated according to a reported protocol. 22 Larvae at 7 days post fertilization ( n = 16) that were exposed to working solutions with daily replacement from 2 hpf were individually transferred to a 24-well plate with 1.5 mL of E3 buffer. The plate was set above a light chamber and covered with black conical plastic that held a video camera on top.…”
Section: Methodsmentioning
confidence: 99%
“…The response of the larvae to dark–light–dark transitions was evaluated according to a reported protocol. 22 Larvae at 7 days post fertilization ( n = 16) that were exposed to working solutions with daily replacement from 2 hpf were individually transferred to a 24-well plate with 1.5 mL of E3 buffer. The plate was set above a light chamber and covered with black conical plastic that held a video camera on top.…”
Section: Methodsmentioning
confidence: 99%
“…Genome editing has been used to model human tumors such as liver cancer [70], paraganglioma [71], skin melanoma [72], and epithelioid sarcoma [73]. Among neurologic diseases, amyotrophic lateral sclerosis [74], epilepsy [75][76][77][78][79] [105,106], inner ear [107][108][109][110][111], vestibular apparatus [111], otoliths [112], brain [89, [113][114][115][116][117], neural tissue [118][119][120][121][122][123][124][125][126][127] and nervous system [128][129][130], heart [131][132][133][134][135][136][137][138][139], cardiomyocytes [140][141]…”
Section: Zebrafish As a Model Object In Studies Using Genome Editingmentioning
confidence: 99%
“…Genome editing has been used to model human tumors such as liver cancer [ 70 ], paraganglioma [ 71 ], skin melanoma [ 72 ], and epithelioid sarcoma [ 73 ]. Among neurologic diseases, amyotrophic lateral sclerosis [ 74 ], epilepsy [ 75 , 76 , 77 , 78 , 79 ], Hirschprung’s disease [ 80 ], autism [ 81 , 82 , 83 , 84 ], spastic paraplegia [ 85 ], restless legs syndrome [ 86 ], insomnia [ 87 ], microcephaly [ 46 ], neurotransmitter function of dopamine [ 88 ], monoamine [ 89 ], and others [ 90 , 91 ]. Cleft lip and cleft palate mutants also have been tested [ 92 ].…”
Section: Genome Editing In Salmonidae and Cyprinidae Aquaculture Fish...mentioning
confidence: 99%
“…Interestingly, the results suggested that in contrast to the human gene, fbxl3a is not essential for brain development, but is a key component of the circadian clock, as is the case in mice. Using the same technology, Rodriguez-Ortiz and Martinez-Torres [6] produced a loss-of-function mutant of hcn2b, one of the two zebrafish paralogs of the HCN2 gene encoding a hyperpolarization-activated cyclic nucleotide gated (HCN) channel. This gene has been found mutated in humans presenting generalized epilepsy, and the zebrafish hcn2b mutant exhibits epileptiform seizures and epilepsy-related behaviors, highlighting the strong evolutionary conservation of the neurochemical processes underlying neuron excitation.…”
mentioning
confidence: 99%